USP28 protects development of inflammation in mouse intestine by regulating STAT5 phosphorylation and IL22 production in T lymphocytes - Le Menn, Gwenaëlle; Pikkarainen, Keela; Mennerich, Daniela; Miroszewska, Dominika; Kietzmann, Thomas; Chen, Zhi (Frontiers in Immunology, 2024)
Ubiquitin-specific proteases (USPs), a large subset of more than 50 deubiquitinase proteins, have recently emerged as promising targets in cancer. However, their role in immune cell regulation, particularly in T cell activation, differentiation, and effector functions, remains largely unexplored. Here, we identify USP28 as a T cell regulator that exerts protective effects in acute intestinal inflammation. Mechanistically, we show that USP28 knockout mice (USP28 -/-) exhibited an increase in total T cells mainly due to an increased CD8+ T cell content. Furthermore, USP28 deficiency resulted in early defects in T cell activation and functional changes. Specifically, we observed a reduced expression of IL17 and an increase in inducible regulatory T (iTreg) suppressive functions. Importantly, activated T cells lacking USP28 showed increased STAT5 phosphorylation. Consistent with this, these mice exhibited increased susceptibility to acute dextran sulfate sodium (DSS)-induced intestinal inflammation, accompanied by elevated IL22 cytokine levels. Collectively, our findings demonstrate that USP28 is essential for T cell functionality and protects mice from acute DSSinduced colitis by regulating STAT5 signaling and IL22 production.